Analysis and Performance Test of Drainage-anchorage Slope Protection Structure with Pervious Concrete - WANG Bin; ZANG Deji; MA Guangjun (Renmin Zhujiang)
In order to prevent the landslide caused by rainfall, this paper studies the slope protection structure with drainage and anchoring function, tests the permeability coefficient, holding force and shear strength of soil interface of drainage and anchorage structure by using porous pervious concrete as anchoring and cementing material, and analyzes numerically the seepage field, shear strength of local soil and slope stability with the slope protection structure. The results show that: the structure can effectively play the role of drainage and anchorage, and the comprehensive effect is better when the porosity is 18%. During rainfall, the rise of phreatic line and the deterioration of rock and soil are relatively slow, which is conducive to the slope stability. After the rainfall stops, the slope can quickly restore to original state. Therefore, the drainage-anchorage slope protection structure has excellent disaster prevention performance.